2001
DOI: 10.1089/10507250150500630
|View full text |Cite
|
Sign up to set email alerts
|

Association of the HLA-DRB1*0301 and HLA-DQA1*0501 Alleles with Graves' Disease in a Population Representing the Gene Contribution from Several Ethnic Backgrounds

Abstract: Graves' disease (GD) is the most frequent cause of hyperthyroidism. Although the etiology is not completely elucidated, there are several lines of evidence suggesting multifactorial mechanisms. Genetic, constitutional, and environmental factors are involved in its pathogenesis. Major histocompatibility complex (MHC) class II alleles have been associated with GD in several populations of distinct ethnic backgrounds and there is increasing evidence supporting an association between GD and HLA-DR3 in Caucasian po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 28 publications
1
37
0
3
Order By: Relevance
“…Besides genes of the MHC class II system such as HLA-DR3 and DQA1 * 0501 on chromosome 6p21 (Yanagawa, Mangklabruks et al, 1993;Zamani, Spaepen et al, 2000;Maciel, Rodrigues et al, 2001), on chromosome 2q33, we found the loci of genes involved in the regulation of T lymphocytes: CD28, CTLA4 and ICOS in which, specifically polymorphisms of the cytotoxic T lymphocyte antigen-4 (CTLA-4) are associated to various autoimmune diseases (Chistiakov and Turakulov 2003;Vaidya and Pearce 2004).…”
Section: Immunoregulator Genesmentioning
confidence: 87%
“…Besides genes of the MHC class II system such as HLA-DR3 and DQA1 * 0501 on chromosome 6p21 (Yanagawa, Mangklabruks et al, 1993;Zamani, Spaepen et al, 2000;Maciel, Rodrigues et al, 2001), on chromosome 2q33, we found the loci of genes involved in the regulation of T lymphocytes: CD28, CTLA4 and ICOS in which, specifically polymorphisms of the cytotoxic T lymphocyte antigen-4 (CTLA-4) are associated to various autoimmune diseases (Chistiakov and Turakulov 2003;Vaidya and Pearce 2004).…”
Section: Immunoregulator Genesmentioning
confidence: 87%
“…In the present study the haplotypes of DRB1* 150101 and DQB1*0602 were highly frequent in the members of maternal pedigree including affected and unaffected Graves' disease, except for the cousin. These haplotypes were not found in the patients with sporadic Graves' disease in Japanese and other ethnic population [7,9,13,24,28]. Because the HLA haplotypes specifically conferred an increased risk for Graves' disease in sporadic form, it is of value to find the differences in HLA typing between familial and sporadic forms of Graves' disease.…”
Section: Discussionmentioning
confidence: 97%
“…Both genetic and environmental factors may affect the development of Graves' disease. Such an autoimmune mechanism could be associated with HLA on chromosome 6p [5][6][7][8][9][10][11][12][13][24][25][26][27][28][29][30][31][32][33] and CTLA-4 on chromosome 2q33 [14][15][16][17][18]. There are several different results regarding HLA haplotypes associated with Graves' disease in Japan [13,28,29,32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the association of GD with DQA1*05 where it was considered a susceptibility marker for GD. Indeed DQA1*05 has been associated with GD in Latvians and Brazilians (Marga et al 2001;Maciel et al 2001). However, it was not found to be associated with GD in the Greek population (Philippou et al 2001) or in African-American patients (Yanagawa and De Groot 1996;Ofosu et al 1996).…”
Section: Discussionmentioning
confidence: 99%